(untitled) (Journal of economic and management development research, 2026)
Against the backdrop of global cultural digitization, the two-dimensional (2D) industry has emerged as a crucial dimension for measuring a country’s cultural soft power. Based on industry data from 2013 to 2024, this study systematically evaluates the export competitiveness of China’s 2D cultural products (including animation, games, and derivatives). The findings reveal that the industry is characterized by "strong foundations but structural imbalances": the domestic market has surpassed RMB 300 billion, yet exported content is notably "juvenile-oriented"; game exports have reached a scale of billions of U.S. dollars but are overly reliant on mobile platforms and markets in the United States, Japan, and South Korea; the derivatives sector has explored effective pathways through the Direct-to-Consumer (DTC) model. The study identifies five major bottlenecks: insufficient original creative capabilities and talent shortages, weak IP ecosystem operations, key technologies being constrained by external factors, inadequate intellectual property protection, and persistent cultural barriers. Through an in-depth analysis of the case of "Genshin Impact," a systematic improvement framework encompassing strategic leadership, technological support, and operational coordination is constructed, providing path guidance for the industry to achieve a critical leap from scale-based exports to value-based exports.